Fat absorption after total gastrectomy in rats submitted to Roux-en-Y or Rosanov-like double-transit technique - Sevá-Pereira,Gustavo (2006)
PURPOSE: Steatorrhea is one of the most common complications in reconstruction after total gastrectomy. Many reconstruction techniques after total gastrectomy have been developed in order to avoid these undesirable effects, but each one of them has some inconvenience. In this experiment, a modified Rosanov technique that keeps duodenal transit, evaluation of fat absorption after gastrectomy was tested. METHODS: Three groups of rats with the same characteristics were used. Total gastrectomy was performed in two groups: one was operated on and transit was reestablished by the Roux-en-Y technique (group Y), while the other was submitted to the modified Rosanov technique (group R). Following surgery, a handmade hyper fatty diet (11% of fat) was offered. A third group (control - group C) was not operated but was submitted to the same conditions of the other groups, and used for reference steatocrit values. The animals underwent laparotomy 14 days after surgery and had their feces collected from cecum to determine their steatocrit by analysis of their values. RESULTS: Steatocrit values for groups R and C (mean 5.16% and 4.15% respectively) were similar (p > 0.1), while group Y had significantly higher values (mean = 28.18%, p = 0.0001 - p < 0,05). This was attributed to the fact that group R animals had their duodenal transit patent, decreasing the complications expected in the Roux-en-Y reconstruction. CONCLUSIONS: Steatorrhea in the modified Rosanov technique was similar to the control group, while Roux-en-Y reconstruction presented higher steatorrhea and fat malabsorption.